KONSEP PENDIDIKAN KELUARGA DALAM ISLAM (Studi Analisis Historis Keluarga Nabi Ibrahim AS) - Nur Muhammad Hamim; Burhanuddin Ridlwan (Menara Tebuireng, 2020)
The family is the smallest group of a society consisting of several members who still have blood ties. The goodness of a family can be influenced by the education in it, because family education is the first and foremost education for a child. As the first and foremost educational institution, the family has an important role to play in introducing and influencing the growth and development of children. Family education aims to create an ideal family so that a loving, mawaddah, and rahmah family is created or a family that loves and cares for each other so that a happy and prosperous family is formed. The patience and fortitude of Prophet Ibrahim in undergoing tests and trials from Allah made him and his family priests and role models for mankind. His example is what made many of his sons promoted by God to be prophets and messengers, even though basically the predicate of prophethood and apostleship is the prerogative of God alone. The focus in this study is: 1) to know the concept of family education in Islam, 2) to know the story of the family of the Prophet Ibrahim As, 3) to know the concept of Family Education in Islam from the story of the family of the Prophet Ibrahim As. This research includes library research. The approach used in this research is a philosophical approach that is an approach that is done to reason and compile a data systematically based on the point of view of historical analysis. Based on the research, it can be known that family education is education that takes place in the family carried out by parents as their duties and responsibilities in educating their children based on the guidance of Islamic teachings. The family of the prophet Abraham is a family that we can use as an example because of the cultivation of oneness as a priority, both in terms of beliefs, words, and deeds. Family education that can be taken from the story of the family of the prophet Abraham is that parents should strive to have and show good qualities and always pray and give advice or a testament of kindness to their children.